Comprehensive management of adults with chronic migraine: Clinical practice guidelines in Mexico. (19th July 2021) - Vélez-Jiménez, Maria-Karina; Chiquete-Anaya, Erwin; Orta, Daniel San Juan; Villarreal-Careaga, Jorge; Amaya-Sánchez, Luis Enrique; Collado-Ortiz, Miguel Ángel; Diaz-García, María Luisa; Gudiño-Castelazo, Manuel; Hernández-Aguilar, Juan; Juárez-Jiménez, Humberto; León-Jiménez, Carolina; Loy-Gerala, María del Consuelo; et al.
Introduction: Migraine is a polygenic multifactorial disorder with a neuronal initiation of a cascade of neurochemical processes leading to incapacitating headaches. Headaches are generally unilateral, throbbing, 4–72 h in duration, and associated with nausea, vomiting, photophobia, and sonophobia. Chronic migraine (CM) is the presence of a headache at least 15 days per month for ≥3 months and has a high global impact on health and economy, and therapeutic guidelines are lacking. Methods: Using the Grading of Recommendations, Assessment, Development, and Evaluations system, we conducted a search in MEDLINE and Cochrane to investigate the current evidence and generate recommendations of clinical practice on the identification of risk factors and treatment of CM in adults. Results: We recommend avoiding overmedication of non-steroidal anti-inflammatory drugs (NSAIDs); ergotamine; caffeine; opioids; barbiturates; and initiating individualized prophylactic treatment with topiramate eptinezumab, galcanezumab, erenumab, fremanezumab, or botulinum toxin. We highlight the necessity of managing comorbidities initially. In the acute management, we recommend NSAIDs, triptans, lasmiditan, and gepants alone or with metoclopramide if nausea or vomiting. Non-pharmacological measures include neurostimulation. Conclusions: We have identified the risk factors and treatments available for the management of CM based on a grading system, which facilitates selection for individualized management.